KOMPETENSI KARYAWAN: ANALISIS PENGETAHUAN, KETERAMPILAN, NILAI, KONSEP DIRI, KARAKTERISTIK PRIBADI DAN MOTIF - Riani, Dini (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Providing professional public services is a joint responsibility between the government and the community, because getting satisfactory services is a community right that must be fulfilled by the government. This research aims to find out how employee competence is described by analyzing the dimensions of knowledge, skills, values, self-concept, personal characteristics and employee motives. This research was conducted using a sample of 50 permanent employees of the Company for approximately 5 months of work. This research uses descriptive analysis of each dimension and statement item submitted, the data collected has met the research data criteria with the validity of the instruments used having met the statistical characteristics of the research. The results of this research show that quality human resources can be seen from the competencies possessed by these human resources. Competence is closely related to the attitudes and behavior that individuals have and display in carrying out their duties and responsibilities in daily life or in carrying out their duties in the organization.